ANALISIS HUBUNGAN PENGETAHUAN, SIKAP DAN PERILAKU TENTANG JAMBAN SEHAT TERHADAP KEPEMILIKAN JAMBAN SEHAT DI DESA PESODONGAN KECAMATAN KALIWIRO KABUPATEN WONOSOBO - admjurnalsiji polibara; Dwi Atin Faidah; Joko Malis Sunarno (Jurnal Ilmiah Medsains, 2020)
One of the goals of the 17 Sustainable Development Goals (SDGs) at the sixth point is to ensure the availability of clean water and sustainable sanitation for everyone. Universal access to adequate sanitation are basic needs and human rights (WHO, 2017). The results of Basic Health Research (Riskesdas) in 2018 showed that the number of households in Indonesia using latrines is 88,2%. One of the districts in Central Java whose coverage of access to healthy latrines is still lowest is Wonosobo district (58%). 1n 2019, based on data from Kaliwiro Public Health Center, the coverage of healthy latrine access in Pesodongan village is still at 91%. The purpose of this study was to analyze the relationship between knowledge, attitude and practice about healthy latrines with ownership of latrines in Pesodongan Village, Kaliwiro Sub-District. This research is a descriptive study with a cross sectional research design approach. The study was conducted in July-August 2020. The sample in this study was 85 head of household. Data collection is done through interview with structured questionnaire. The data is processed through the process of cleaning, editing, coding, tabulating and entry and then performed statistical analysis using SPSS version 19.0. The statistical design used is bivariate analysis. The results showed that most research respondents are in the age group 41-60 years old (72,95%), elementary school graduates (72,9%), work as farmers (89,4%), monthly income is still below the UMK (97,6%), already have latrines (84,7%), latrines that meet health requirements only reach 43 latrines (59,7%), have a good level of knowledge (65,9%), have good attitudes (90,6%) and have good practice positive ones (91,8%). There is a relationship between knowledge of healthy latrines and ownership of healthy latrines and there is no relationship between attitudes and practice about healthy latrines and ownership of healthy latrines in Pesodongan Village. It is hoped that there will be counseling regarding the importance of healthy latrines to meet basic sanitation needs. In addition, strengthening the latrine program either independently or with government assistance. Keywords: healthy latrines, ownership of latrines, knowledge, attitude, practice